An Interactive Courseware to Teach Mathematics for Children with Hearing Disabilities - Suriati Khartini, Jali; Noor Shazazila Aznin, Mior Aziz; Mohamad Imran, Bandan; Noralifah, Annuar; Noor Hazlini, Borhan (2012)
This paper describes an interactive learning CD-based courseware that has been developed to assist school teachers using an effective approach to teach mathematics to special students in particular, hearing impaired students. As such, it overcomes the limitations of current e-learning systems that tend to ignore marginalised groups such as the disabled. A courseware module has been introduced to teach numbers, counting and basic mathematical operations to deaf students aged 7-10 years old. Students are able to learn sign language whereby animations, graphics, audios and videos are integrated to create the signs. Unlike traditional method of teaching; which tends to be teacher-centred and student remain as passive recipients; students are kept actively involved in the learning process and the teacher acts as a guide to facilitate their learning. Interactive activities and multimedia games are among the extra features that are employed allowing teachers to measure their students’ comprehension. The courseware has been experimented for teaching in a local school for the hearing impaired. Teachers provide positive feedbacks after implementation which shows that the courseware could be a potential assistive tool to teach this special group of students.